2013
DOI: 10.1590/s1516-35982013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Cattle farmers: profile and speech content analysis while undergoing training to adopt artificial insemination in Goiás State, Brazil

Abstract: -This study was undertaken to verify major issues present in the discourse of cattle farmers when discussing the use of artificial insemination (AI). Seventy-one beef and dairy cattle farmers in the state of Goiás, Brazil, were interviewed using semi-structured questionnaires during AI training courses in 2010 and 2011. Data analyses were done using the classic method of textual speech content analysis, performing the pre-analytical, analytical and inferential stages. The written questions were separated in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Despite the large number of farmers that work exclusively with milk cattle, the use of reproductive biotechnology such as FTAI is scarce. These results confirmed the reports of Gordo et al (2013), who analyzed the use of AI among beef or dairy cattle in the state of Goiás, Brazil, and also found that more farmers only used conventional artificial insemination. The farmers perceived that the difficulties in implementing AI went beyond simply depositing semen in the genital organ of the cows.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Despite the large number of farmers that work exclusively with milk cattle, the use of reproductive biotechnology such as FTAI is scarce. These results confirmed the reports of Gordo et al (2013), who analyzed the use of AI among beef or dairy cattle in the state of Goiás, Brazil, and also found that more farmers only used conventional artificial insemination. The farmers perceived that the difficulties in implementing AI went beyond simply depositing semen in the genital organ of the cows.…”
Section: Discussionsupporting
confidence: 89%
“…The corpus was made up of 1,021 ECU, of which 20.7% were discarded (answers without nexus, illegible handwriting, and duplicated answers). According to Gordo et al (2013), three main categories can originate from corpus analysis: basic necessities for adopting AI (30.24% of all ECU), personal motivation for adopting AI (43.26% of all ECU), and social influence for adopting AI (26.46% of all ECU).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although speech analysis, as other qualitative approaches, are not common in the animal sciences, it has a history of more than 60 years of use in communication, journalism, sociology, psychology, business, and other disciplines (Neuendorf, 2017). Nevertheless, some researches have inserted these methodologies in the context of animal science and as a diagnostic tool for genetic animal conservation (Gordo et al, 2013;Solano et al, 2013;Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%